THEORETICAL STUDIES OF 238U-230TH-226RA AND 235U-231PA DISEQUILIBRIA IN YOUNG LAVAS PRODUCED BY MANTLE MELTING - Zou H.; Zindler A. (My University, 2000)
This paper provides ready-to-use equations to describe variations in uranium-series (U-series) disequilibrium as a function of elemental distribution coefficients, melting porosity, melting rate, and melting time. The effects of these melting parameters on U-series disequilibria are quantitatively evaluated in both an absolute and relative sense. The importance of net elemental fractionation and ingrowth of daughter nuclides are also described and compared in terms of their relative contributions to total U-series disequilibrium. In addition, we compare the production of U-series disequilibrium during mantle melting to trace element fractionations produced by melting in a similar context. Trace element fractionations depend externally on the degree to which a source is melted, whereas U-series disequilibrium depends upon both the degree and rate of melting. In contrast to previous models, our approach to modeling U-series disequilibrium during dynamic melting collapses simply to a description of trace element behavior during dynamic melting when the appropriate decay terms are omitted. Our formulation shows that extremely small degrees of melting, sometimes called upon to explain observed extents of U-series disequilibrium, are not always required.